Effects of exposure to a cafeteria diet during gestation and after weaning on the metabolism and body weight of adult male offspring in rats. Issue 8 (28th April 2014) - Mucellini, Amanda Brondani; Goularte, Jéferson Ferraz; de Araujo da Cunha, Ana Carla; Caceres, Rafael Corrêa; Noschang, Cristie; da Silva Benetti, Carla; Silveira, Patrícia Pelufo; Sanvitto, Gilberto Luiz
<x content-type="archive" xml:space="preserve">Abstract</x> In the present study, we investigated whether maternal exposure to a cafeteria diet affects the metabolism and body composition of offspring and whether such an exposure has a cumulative effect during the lifetime of the offspring. Female rats were fed a control (CON) or a cafeteria (CAF) diet from their own weaning to the weaning of their offspring. At 21 d of age, male offspring were divided into four groups by diet during gestation and after weaning (CON-CON, CON-CAF, CAF-CON and CAF-CAF). Blood was collected from dams (after weaning) and pups (at 30 and 120 d of age) by decapitation. CAF dams had significantly greater body weight and adipose tissue weight and higher concentrations of total cholesterol, insulin and leptin than CON dams (Student's t test). The energy intake of CAF rats was higher than that of CON rats regardless of the maternal diet (two-way ANOVA). Litters had similar body weights at weaning and at 30 d of age, but at 120 d, CON-CAF rats were heavier. At both ages, CAF rats had greater adipose tissue weight than CON rats regardless of the maternal diet, and the concentrations of TAG and cholesterol were similar between the two groups, as were blood glucose concentrations at 30 d of age. However, at 120 d of age, CAF rats were hyperglycaemic, hyperinsulinaemic and hyperleptinaemic regardless of the maternal diet. These findings suggest that maternal obesity does not modulate the metabolism of male offspring independently, modifying body weight only when associated with the intake of a cafeteria diet by the offspring.